Relationship Level Of Knowledge And Community Attitude To Selection Of Traditional Medicine To Prevent Covid-19 In Central Jakarta - Nur Cahyanti, Eka (Riviera Publishing, 2022)
COVID-19 is a disease that attacks the human respiratory system and has a rapid spread of positive cases in Indonesia. Therefore, prevention efforts are needed, one of them by keeping the immune system using herbal immunomodulators. However, the use of this herbal immunomodulator is cannot be separated from the level of knowledge and attitudes of the community. This study aims to determine the level of knowledge and attitudes of the community and the relationship between knowledge and attitudes in efforts to prevent COVID- 19 using herbal immunomodulators in the community. This type of research is descriptive using a cross sectional design with the research instrument used is an online google form questionnaire which is distributed through the Whatsapp application. The level of public knowledge regarding the selection of traditional medicines in the prevention of Covid-19 using Herbal Immunomodulators in the Central Jakarta area was 96.3% of respondents rated Good, 2.8% of respondents included in the predicate of sufficient knowledge and 0.9% of respondents who entered the poor category. The level of good attitude is as much as 88%, 8.3% of respondents are included in the predicate enough and 3.7% are included in the less category. The level of good behavior is 87%, 10.2% is included in the predicate enough and 2.8% is included in the less category. Based on statistical tests through the chi square test, the results showed that there was a relationship between the level of knowledge and attitudes towards COVID-19 prevention behavior using herbal immunomodulators in the Central Jakarta Region with a p-value of 0.000. The correlation between knowledge, attitudes, and behavior is found that a person's knowledge is influenced by experience and the environment which is then believed to lead to motivation. A person's behavior will last a long time if it is based on knowledge. Good public knowledge can affect a person's attitude, especially in the prevention of COVID-19